Fisherman community health behavior in facing COVID 19 pandemic at Port III, Pamekasan Regency - Budijanto Budijanto; Ifan Deffinika; Alfyananda Kurnia Putra (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2022)
The problem of slum and squatter settlement is caused by improper environmental planning. This study examines socioeconomic determinants of human health by adopting concepts of population morbidity from Mosley and Chen. The purpose of this study was to analyze various conditions behind the low environmental health behavior of fishermen's households in the face of the COVID 19 pandemic. This study used a quantitative approach with a population from fishermen's households. The samples were selected purposively by considering economic and spatial conditions. Primary data collection was carried out through structured and in-depth interviews. The dependent variable in this study was individual disease control, particularly the standard health protocol during the COVID 19 pandemic. Meanwhile, the independent variable of the population health behavior was measured using a Likert scale. Those independent variables consisted of hand hygiene, the use of masks, and maintaining distance. The results showed that as many as 30 percent of fisherman households were classified as the population with good quality health behavior, 43.33 percent of the population presented moderate-quality health behavior, and 26.77 percent of the population had poor quality health behavior. Those behaviors might be caused by their relatively low perception and knowledge on the importance of maintaining health during the COVID 19 pandemic.